Aspectos distributivos do IPTU e do patrimônio imobiliário das famílias brasileiras - Pedro Humberto Bruno de Carvalho Jr. (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The paper seeks to analyze the distribution of real estate assets among Brazilian families and IPTU-property tax-their main form of taxation. The text points out that real estate property usufruct is more concentrated than family income itself, despite the fact that IPTU boasts a dubious behavior, from a distributive standpoint. The tax burden is heavier on wealthier families, since only a few low-income families actually pay property tax. However, when only the universe of actual taxpayers is examined, it is observed that the tax structure is highly regressive, with poorer taxpayers more likely to undergo a heavier tax burden. The main causes pointed out in the text are poor administrative management, outdated and regressive official real estate assessment versus property market values and the lack of a comprehensive coverage of tax maps and inventories of poor dwelling units. The possibility of adoption of progressive tax rates, introduced by Constitutional Amendment no 29 of 2000, did little to alter IPTU distribution in the municipalities that embraced it, for they were not duly calibrated in accordance with the distribution of the properties market values to be taxed. Additionally, the paper demonstrates that a broad IPTU exemption policy, together with poor administrative and assessorial quality end up exempting middle and higher-income families from paying property tax. A tax reform devised to increase tax progressiveness in Brazil, increasing property tax bills and easing the tax weight on consumption, must be perceptive of the distributive aspects of IPTU, instead of merely focusing on an increase or progression oftax levy rates.
Keywords: H23; H24; H71; R52; 330; Grundbesitz; Grundsteuer; Brasilien